Studi Pelacakan Tenaga Kerja Lulusan SMK Pada Industri Di Kabupaten Sidoarjo - Hafid Rahmandan; Mohamad Riyandi Badu; Andi Maga Umara; Sugeng Pramudibyo; Esta Larosa; Aristi Ayuningsi Ode Asri; Musfir Rizal Pratama (Jambura Journal of Engineering Education, 2024)
The background of this study is triggered by many problems in the working world and One of them is the large number of vocational graduates that become unemployed and This study aims to analyzing performance of employees based on their working time, potential, and quality of their almamater.  This study uses ex post facto method with quantitative approach, while for the research desain using a factorial design. The results showed performance employees with high working period 83,35 higher than moderate working periode 82,48 and low working periode 81,26; performance employees with high potential 83,89 higher than moderate potential 82,00 and low potential 81,18; and performance with quality of their almamater/non accreditation A 83,00 higher than accreditation A 82,15